Acute haemothorax and pleuropulmonary blastoma: Two extremely rare complications of extralobar pulmonary sequestration - Alessandra Preziosi; Anna Morandi; Francesca Galbiati; Paolo Scanagatta; Stefano Chiaravalli; Anna Maria Fagnani; Antonio Di Cesare; Francesco Macchini; Ernesto Leva (Elsevier, 2022)
Extralobar bronchopulmonary sequestration (eBPS) is a congenital lung malformation characterized by non-functional lung tissue with no connection with the bronchial tree, receiving systemic blood supply and covered by its own visceral pleura. It is mostly asymptomatic, however it can rarely get complicated with infections and neoplastic degeneration. Its management is still debated: many authors suggest observation for asymptomatic cases and intervention only in case of symptoms, others advocate surgery even in asymptomatic patients. Pleuropulmonary blastoma (PPB) is a rare malignant sarcomatous neoplasm, representing the most common primary lung malignancy in children. Typically, PPB is associated with congenital pulmonary airway malformation (CPAM). eBPS is rarely associated with PPB. We report a case of a previously healthy three-year-old boy presented to our emergency room with massive hemothorax after a low-energy chest trauma. Imaging revealed active thoracic bleeding by an anomalous artery arising from the celiac tripod, and an irregular mass in the lower right hemithorax. After performing biopsy, pathologic examination revealed a PPB. The patient underwent four cycles of chemotherapy before surgery. The operative findings revealed a right supradiaphragmatic extralobar mass, with no communication with the bronchial tree, strictly adherent to the right middle lobe. After mass excision, histological analysis confirmed the diagnosis of PPB type 2. The patient underwent postoperative chemotherapy. No recurrence nor metastasis were noted during the current follow-up. DICER-1 research revealed biallelic mutation on the tumor and on the surrounding normal tissue. We reviewed the literature concerning PPB and BPS. Based on these data, we would recommend intervention even in case of asymptomatic eBPS.